2013
DOI: 10.1673/031.013.1201
|View full text |Cite
|
Sign up to set email alerts
|

Interactions betweenMeteorus pulchricornisandSpodoptera exiguaMultiple Nucleopolyhedrovirus

Abstract: Baculoviruses may interact with parasitoids in the same host. A previous study has shown that infection of larvae with Spodoptera litura nucleopolyhedrovirus (SpltNPV) was deleterious to the survival and development of Meteorus pulchricornis (Wesmael) (Hymenoptera: Braconidae). In this paper, the interactions between M. pulchricornis and Spodoptera exigua multiple nucleopolyhedrovirus (SeMNPV) in Spodoptera exigua (Hübner) (Lepidoptera: Noctuidae), a permissive host of the virus and parasitoid, were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…There is also no significant difference in the developmental period (egg to pupae) of parasitoids that emerged from SoNPV-treated and untreated larva. These results find support from earlier findings of Guo et al(2013) who reported that the development time of the M. pulchricornis that emerged from SeMNPV-infected S. exigua was not affected by the virus.…”
Section: Resultssupporting
confidence: 92%
“…There is also no significant difference in the developmental period (egg to pupae) of parasitoids that emerged from SoNPV-treated and untreated larva. These results find support from earlier findings of Guo et al(2013) who reported that the development time of the M. pulchricornis that emerged from SeMNPV-infected S. exigua was not affected by the virus.…”
Section: Resultssupporting
confidence: 92%
“…Furthermore, the ingestion of SeMNPV OBs by parasitoids increased the number of parasitoid offspring that successfully emerged from the host. 37 By contrast, HearNPV infection prolonged the development of Microplitis mediator. 30 The results of the current study showed that HearNPV also prolonged the development time (from larvae to adults) of C. chlorideae and negatively affected C. chlorideae reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…These natural enemies have also been used in combination 27 . However, not all combinations of baculoviruses and parasitoid wasps have resulted in improved pest control, which may depend on inoculum concentration 37 . In this study, the combined use of C. chlorideae with a high concentration of HearNPV OBs revealed that the mortality of H. armigera larvae infected with HearNPV and parasitized 24 h later (treatment 3, V + P) was significantly higher than that caused by HearNPV or C. chlorideae alone, whereas the mortality in treatment 4 (P + V) was not higher than that caused by parasitism alone.…”
Section: Discussionmentioning
confidence: 99%
“…Parasitism by parasitic wasps has been demonstrated to affect NPV in caterpillars. For example, the use of Meteorus pulchricornis as a biocontrol agent improved the insecticidal effect of high‐dosage SeMNPV against beet armyworms (Guo, Fang, Zhong, & Liu, ). Furthermore, the use of Microplitis demolitor increased the lethality of the Helicoverpa armigera NPV (Murray, Monsour, Teakle, Rynne, & Bean, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the use of Microplitis demolitor increased the lethality of the Helicoverpa armigera NPV (Murray, Monsour, Teakle, Rynne, & Bean, ). Conversely, however, M. pulchricornis was shown to reduce the biological activity of low‐dosage SeMNPV (Guo et al, ). These results indicate that the effect of parasitic wasps on NPV is determined by the virus type, parasitoid species, viral dose and other factors (Escribano, Williams, Goulson, Cave, & Caballero, ; Stoianova, Hernandez, & Caballero, ).…”
Section: Introductionmentioning
confidence: 99%